Seasonal Variations of the Urban Thermal Environment Effect in a Tropical Coastal City - Yao Yuan; Chen Xi; Qian Jing; Ndayisaba Felix (Advances in Meteorology)
Shenzhen city was selected to analyze the Surface Urban Heat Island (SUHI) variations based on land surface temperature (LST) in four different seasons of 2015. UHI intensity (UHII) as an indicator of SUHI was established and the method of density segmentation was utilized to classify the SUHI after LSTs were normalized. The gravity center model of UHII and Moran’s I (a spatial autocorrelation index) were used to analyze the spatiotemporal variations of SUHI. Results indicated that LST was higher in the west than in the east of the city. The values of UHII were higher in spring and summer and lower in autumn and winter. Five profiles were drawn to analyze the distribution of UHII in different seasons, and it was found that the No. 1 path profiles, corresponding to the western urban development axis, had higher UHII than other path profiles. The center of UHII gravity shifts converged in the Longhua, Baoan, and Nanshan Districts throughout the four seasons and Moran’s I values were higher in summer and spring. From the UHII’s spatial distribution pattern analysis, a spatially discontinuous pattern was observed in four seasons; there was a compact pattern of high temperature zones.